Communication Between Autophagy and Insulin Action: At the Crux of Insulin Action-Insulin Resistance? - Frendo-Cumbo, Scott; Tokarz, Victoria L.; Bilan, Philip J.; Brumell, John H.; Klip, Amira (Frontiers in Cell and Developmental Biology, 2021)
Insulin is a paramount anabolic hormone that promotes energy-storage in adipose tissue, skeletal muscle and liver, and these responses are significantly attenuated in insulin resistance leading to type 2 diabetes. Contrasting with insulin’s function, macroautophagy/autophagy is a physiological mechanism geared to the degradation of intracellular components for the purpose of energy production, building-block recycling or tissue remodeling. Given that both insulin action and autophagy are dynamic phenomena susceptible to the influence of nutrient availability, it is perhaps not surprising that there is significant interaction between these two major regulatory mechanisms. This review examines the crosstalk between autophagy and insulin action, with specific focus on dysregulated autophagy as a cause or consequence of insulin resistance.